Analisis Kinerja Keuangan Baznas Provinsi Bengkulu Dengan Metode Iszm - Citra, Onti Laura; Hariyadi, Rizky (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
The application of accountability and transparency in published financial reports is very important for society so that people are able to assess the financial performance of zakat institutions in collecting, managing and distributing zakat funds. The aim of this research is to measure and analyze the level of efficiency and capacity of BAZNAS financial performance in Bengkulu Province using International Standard Zakat Management (ISZM) method. The research method used is a quantitative method with a quantitative descriptive approach. Data collection techniques are by taking financial report data on the BAZNAS Bengkulu Province website. The types of data from this research consist of primary data and secondary data. Secondary data in this research is a type of time series data using a time span of 1 year, namely 2022. Secondary data collection techniques are obtained through various sources such as reports, books, journal articles, websites related to the research object.